A Unified Approach to Facial Contours and Volume Correction: The Role of the Cheek and the Chin - Amir Moradi, MD; Jose Raul Montes, MD; Shannon Humphrey, MD; Lisa D. Grunebaum, MD; Dario Bertossi, MD; Elena Dimitrijevic, PhD; Sara Sangha, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. Facial proportions and contours influence perceptions of beauty and youthfulness. In particular, the shape and definition of the midface and lower face impact the overall appearance of the face. Methods:. This review provides anatomical evidence to support a holistic approach to facial analysis and rejuvenation that starts with assessment and treatment of the midface and lower face to create an aesthetically desirable facial balance. Results:. The cheek and chin can be considered “anchors” or starting points within full-face treatment because of the noticeable impact of their treatment on the definition and contour of the entire face. Age-related changes in the cheek and chin affect overall facial appearance and can produce unintended facial emotional attributes such as looking tired, angry, or sad. Patients seek facial aesthetic treatment typically for a global improvement such as revitalization or genderization of facial features. Best practices in aesthetics have evolved from treatment of individual areas to a holistic paradigm that uses multimodal therapy to improve overall facial emotional attributes. Hyaluronic acid fillers are useful for volume replacement and smoothing abrupt transitions that develop with age throughout the midface, chin, and jaw. A combination of hyaluronic acid filler for volume restoration and sodium deoxycholate and/or onabotulinumtoxinA for volume reduction where appropriate may optimize lower facial contour. Conclusions:. This review highlights the importance of facial angles and contours as well as the significance of panfacial assessments and treatment, focusing on the relationships within areas of the face, specifically the midface and lower face, to optimize results.